2005
DOI: 10.1111/j.1365-2443.2006.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene order in human α‐globin locus is required for their temporal specific expressions

Abstract: The human α α α α -globin cluster represents a unique model of transcriptional regulation and provides challenges to the current understanding of interactions between distal and proximal regulatory elements. Although the gene proximal regions are believed to possess almost all the necessary elements for temporal and spatial specificity of gene transcription, it is still not clear whether the relative distance of embryonic ζ ζ ζ ζ -and fetal /adult α α α α -genes to their distal regulatory element α α α α -URE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Assessing the affects of alterations to the construct can, as shown here, be more easily tested in the zebrafish than a mammalian model. The loci’s genomic context, presence of “intervening” sequence between the LCR and proximal promoter/coding sequence and the absence of additional genes in the region have all been investigated and/or shown to have an effect on globin switching (de Laat and Grosveld, 2003; Flint et al, 2001; Higgs et al, 2008; Li et al, 2002; Noordermeer and de Laat, 2008; Palstra et al, 2008; Tang et al, 2006). Determining the role(s) of these additional regulatory elements can provide a better understanding of globin switching.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the affects of alterations to the construct can, as shown here, be more easily tested in the zebrafish than a mammalian model. The loci’s genomic context, presence of “intervening” sequence between the LCR and proximal promoter/coding sequence and the absence of additional genes in the region have all been investigated and/or shown to have an effect on globin switching (de Laat and Grosveld, 2003; Flint et al, 2001; Higgs et al, 2008; Li et al, 2002; Noordermeer and de Laat, 2008; Palstra et al, 2008; Tang et al, 2006). Determining the role(s) of these additional regulatory elements can provide a better understanding of globin switching.…”
Section: Discussionmentioning
confidence: 99%
“…1B). However, the results of the gene inversion studies of Tang et al (40) and of Tanimoto et al (41) showed that when the embryonic genes were moved to the most distant positions from the upstream regulatory regions, they were thereby rendered transcriptionally silent but the adult genes were expressed at all stages. The reasons given for these findings were based upon the presumed disruption of interactions with promoters within the upstream regulatory regions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the earlier reports of Wong et al (39) about the occurrence of adult hemoglobin in addition to embryonic hemoglobins in early mouse embryos support the findings of Leder et al The normal order of genes in both the Rand β-globin gene clusters in relation to the upstream regulatory regions (Figure 1C) has been considered to be of primary importance for the correct temporal expression of the embryonic, fetal, and adult hemoglobins (Figure 1B). However, the results of the gene inversion studies of Tang et al (40) and of Tanimoto et al (41) showed that when the embryonic genes were moved to the most distant positions from the upstream regulatory regions, they were thereby rendered transcriptionally silent but the adult genes were expressed at all stages. The reasons given for these findings were based upon the presumed disruption of interactions with promoters within the upstream regulatory regions.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth emphasizing once again that the correct switching of globin gene expression is possible only in the context of existing gene clusters. A simple change in the order of the genes, relative to the super-enhancer (for example, when the entire gene cluster is inverted), as well as the inclusion of an additional gene in the cluster, leads to serious disruptions in the switching process of both alphaand beta-globin genes [67][68][69]. In experiments with ectopic expression, the adult betaglobin gene controlled by the LCR was expressed at an early stage of development, when this gene should not be expressed.…”
Section: Functional Role Of Gene Clustering In Vertebrate Cellsmentioning
confidence: 99%